2021
DOI: 10.54203/scil.2021.wvj69
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Rabbit Production under the Global Warming Conditions in Southern Mediterranean Region

Abstract: There is still a wide gap between meat demand and meat production in Egypt. This gap is becoming larger due to the direct and indirect impacts of global warming that negatively influence the grazing area and the performance of livestock. In this context, rabbits are considered as an alternative source for animal-origin meat. In the Southern Mediterranean region, the most obvious problem encountering rabbit production is the hot waves during the summer, especially during the last decades. The narrow thermo-neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Buffalo are one of the social animals that prefer to live in a herd. However, heat waves, diseases, and restricted space stresses can lead to oxidative stress (Odore et al 2011 ; El Sabry et al 2021 ; 2022 ), which is commonly associated with the incidence of several health problems, such as retained placenta, udder edema, and mastitis. Consequently, this deterioration in health status can lessen the production performance of animals (StarvaggiCucuzza et al, 2014 ).…”
Section: Stocking Density Affects Social Behavior and Welfare Indicesmentioning
confidence: 99%
“…Buffalo are one of the social animals that prefer to live in a herd. However, heat waves, diseases, and restricted space stresses can lead to oxidative stress (Odore et al 2011 ; El Sabry et al 2021 ; 2022 ), which is commonly associated with the incidence of several health problems, such as retained placenta, udder edema, and mastitis. Consequently, this deterioration in health status can lessen the production performance of animals (StarvaggiCucuzza et al, 2014 ).…”
Section: Stocking Density Affects Social Behavior and Welfare Indicesmentioning
confidence: 99%
“…The deleterious effect of heat stress on the reproductive traits in mammals is well documented ( 26 , 27 ). Since rabbits are susceptible to heat stress conditions ( 3 ), lower litter traits are usually associated with an increase in ambient temperatures ( 28 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rabbit is a good source of meat and can contribute to filling the gap between the production and consumption of animal protein. Nevertheless, rabbit is susceptible to heat stress (HS) conditions ( 2 , 3 ). This change in atmospheric temperature will generate heat stress conditions in tropical and subtropical regions like the south of the Mediterranean, especially in the open production system, which is the most common farm type in Egypt ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…When animals are exposed to high temperatures above 25-30°C, their body temperature rises. Rabbits try to balance the excessive heat load using different means to dissipate it as much as possible (Abdel-Hamid and Dawod, 2015;El Sabry et al, 2021;Mutwedu et al, 2021).…”
Section: Physiological Indicatorsmentioning
confidence: 99%
“…J., 12 (4): 405-417. DOI: https://dx.doi.org/10.54203/scil.2022.wvj51 reactions affect rabbits by disrupting their physiological functions and behavioral performance (El Sabry et al, 2021;Mutwedu et al, 2021;Liang et al, 2022), such as impairment of appetite, alteration of the feed efficiency and growth performance, milk yield, and reproduction in rabbits, leading to considerable production and economic losses (Plá et al, 1994;Zeferino et al, 2011). It was reported that a reduction of body temperature to 1°C or less suppresses both physiological and growth performance in livestock (Manca et al, 2018).…”
Section: Introductionmentioning
confidence: 99%